Comparison of the Effectiveness of Mindfulness Intervention and Cognitive-Behavioral Game Therapy on the Psychological Capital of Female - Mahnaz Shokri; Nabiollah Akbar Nataj Shub; Jamal Sadeghi; Arsalan Khanmoham Otaghsara (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk, 2024)
Introduction: Several factors influence students' behaviors and develop motivation. Meanwhile, cognitive factors such as psychological capital play a more prominent role than others, and it is crucial to understand the factors that affect them. The current research purpose was to compare the effectiveness of mindfulness intervention and cognitive-behavioral game therapy on the psychological capital of female first-secondary school students in Amol City. Methods: The research method was semi-experimental with a pre-test-post-test design with a control group. The statistical population included all the female students of the first secondary school of the seventh grade of the public schools of Amol City in the academic year of 2023. Among them, 45 people were selected by the available sampling method and were replaced randomly and by lottery in two experimental and control groups (30 individuals in the experimental group and 15 people in the control group). The people attending the first experimental group received mindfulness intervention (8 sessions) and two sessions per week for 60 minutes, and the second experimental group received cognitive-behavioral game therapy intervention (10 sessions) and two sessions per week for 30 minutes. The questionnaire used in this research included psychological capital. The study data was analyzed using the repeated measures analysis of variance (ANOVA) method. Results: The findings showed that mindfulness and cognitive-behavioral game therapy affected the psychological capital of female students of the first secondary school in Amol City (P < 0.01). Also, mindfulness training on psychological capital was more effective than cognitive-behavioral game therapy (P < 0.01). Conclusions: Although both methods of mindfulness training and play therapy improved students' psychological capital, the approach and method used in each are different. Mindfulness training focuses more on awareness and the presence of the mind in the present moment. At the same time, play therapy focuses more on strengthening psychological skills and abilities through interactive activities and games, which can better capitalize on increased psychological.